Uma avaliação de viabilidade financeira no uso da energia solar fotovoltaica apoiada pela resolução ANEEL 482/2012 sobre geração distribuída no setor elétrico do Brasil - Carvalho, Francisco Ivanhoel Aguiar de (2014)
This dissertation is to examine, through an economic analysis the impacts of the implementation of ANEEL Resolution 482/2012 laying down the general conditions for the access of micro and minigeneration conferred to the distribution systems of electric power from the method of energy compensation. As a way to evaluate the economic feasibility for implementation of the methodology in the Brazilian electric sector, the survey was conducted on Photovoltaic Systems Connected to the Network - SFCR by building two scenarios: (i) proposal for self-sufficiency in photovoltaic generation, paying availability cost of distribution and taxes due and (ii) where the aim is to use photovoltaic in order to cancel the "sun time" in alternative generation, also paying costs availability and taxes. A model KD140SX-UPU panel was used, for their benefit cost and compatible with lifetime-researched bibliography. Also was used to rate the residential consumer B1 approved by ANEEL for COELCE through the approving resolution 1.711/2014, which is 0.35922 R$ / kWh plus taxes. The results of the economic analysis for the consumer proved attractive only for scenario (ii) because the internal rate of return was higher than the hurdle rate and the average payback time was calculated between 7 and 10 years. About the impact of the power utility, the results indicated that the adhesion of potential customers, probably the last consumption range (greater than 220 kWh) could lead to economic effects in Net Operating Revenue, which may be the subject of future research, but that the grid would be affected positively, since the decentralized load would bring a loss reduction, stability of supply voltage and, in some circumstances, delay of future investments. Furthermore, it is noted that the price impact could reflect positively to the captive consumers, since the excess energy injected into the network, provide a better study of the planning area of engineering companies, better sizing electrical equipment and enabling best use of these assets, optimizing their lifetime and contributing to the low tariffs.